Effects of arterial wall distensibility on the near wall flowfield in a model of a human carotid bifurcation - Giddens, Don P.; Jones, Steve A.; Anayiotos, Andreas (My University, 1991)
Arterial wall distensibility is believed to be of secondary importance to the general flowfield of the human carotid artery. However, it has been reported that it may have greater influence on the near wall flow variables such as shear stress and separation zones. To further investigate this factor two models of the carotid bifurcation were constructed. One was rigid and one was made of a compliant material and produced approximately the same degree of wall motion as that occurring in vivo. Each model was placed in a pulsatile flow system and velocities and shear stresses were measured with a single component laser system along the diameter at different axial locations. Wall motion was also measured and the maximum diameter change varied between 4-7% around the model. Lower shear stresses were observed at the locations of measurement in the compliant model. The separation zone during systole was observed to be more extensive radially and axially, upstream of the mid-sinus for the compliant model. In addition, the separation zone was found to be more extensive in time during the pulsatile cycle. These observations in comparison with previously reported data at these locations may be important in a hemodynamic theory of atherogenesis.
Keywords: Biomechanics; Blood-vessels; Cardiovascular system; Hemodynamics